2020
DOI: 10.1186/s12879-020-05076-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous community-acquired PVL-producing Staphylococcus aureus mediastinitis in an immunocompetent adult – a case report

Abstract: Background Mediastinitis caused by hematogenous spread of an infection is rare. We report the first known case of community-acquired mediastinitis from hematogenous origin in an immunocompetent adult. This rare invasive infection was due to Panton-Valentine Leucocidin-producing (PVL+) methicillin-susceptible Staphylococcus aureus (MSSA). Case presentation A 22-year-old obese man without other medical history was hospitalized for febrile precordial chest pain. He reported a cutaneous back abscess 3 weeks befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, these multifocal features were not confirmed in a larger cohort of 16 patients with PVL + Sa pneumonia from the same location 31 . Few case reports have mentioned multiple-site infections or unconventional septic sites, including prostatic or renal abscesses or mediastinitis [32][33][34] .…”
Section: Main Complicationsmentioning
confidence: 99%
“…However, these multifocal features were not confirmed in a larger cohort of 16 patients with PVL + Sa pneumonia from the same location 31 . Few case reports have mentioned multiple-site infections or unconventional septic sites, including prostatic or renal abscesses or mediastinitis [32][33][34] .…”
Section: Main Complicationsmentioning
confidence: 99%
“…In addition, mediastinitis as a complication of primary skin infections is also a rare entity. Brisset et al ( 1 ) reported a case of Staphylococcus aureus mediastinitis in an immunocompetent adult following back skin abscess. To the best of our knowledge, the present case is the second report of such a case of mediastinitis secondary to hematogenous spread following skin infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mediastinitis, which is an inflammation of the chest region between the lungs, develops mostly due to a deep wound infection of the sternum, pneumonia, perforation of the esophagus, or descending necrotizing mediastinitis resulting from ear-nose-throat infections ( 1 ). Very rarely, mediastinitis can occur from hematogenous spread, and is usually a complication of the health care received ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mediastinitis is mainly a downward necrotizing mediastinitis caused by deep sternal wound infection, esophageal perforation or ENT infection [2] . Researchers had reported the treatment of thoracic esophageal rupture and with concomitant empyema and mediastinitis [3,4] , but esophagus rupture caused by high pressure gas with concomitant empyema and mediastinitis had never reported.…”
Section: Introductionmentioning
confidence: 99%